The Study on Potential and Impacts of Short-Term Room Rental for Tourism in Thailand - Manirochana, Nattapat; Junead, Jutatip; Jamnongchob, Angsumalin (KKBS Journal of Business Administration and Accountancy, 2020)
This research project aims to study the current situation of short-term rentals for tourism in Thailand, including Thai entrepreneurs’ potential in this business. This research project also studied the customer behavior and effects of the short-term rental for tourism in Thailand. These results will be used as a recommendation to develop short-term rentals in Thailand. This research’s sampling group is 1,127 tourists using the service of the short-term rental for tourism in Thailand. This research also used the questionnaire as the research tool, with 5 level rating scales arranged in ascending order. The reliability of the questionnaire is equal to .76. The key informants have consisted of government officers, Thai entrepreneurs, and tourists. Individual Interviews, group interviews, and 187 people in participation observation are the research methods. The statistical analysis for the research question is a percentage, Mean and Standard Deviation. Qualitative research methods are also used in this project. The results of this project are as follows: The host of short-term rentals for tourism in Thailand is increased according to the tourist demand in Thailand, especially in the top traveling destination in Thailand such as Bangkok, Pattaya, Phuket, and Chiang Mai Province. The potential of The Thai entrepreneur in short-term rentals for tourism in Thailand is excellent. The strong point is good accommodations, hospitality, good hosting, multiple choice for rental and living, convenience for many activities, and privacy. The tourist’s top requirement is the unique place, low price, good experience, privacy, and home alike. The Effect is the low rental standard, unfair competition. Tricky service, misused buildings, disturb, and the Thai government cannot take any income tax from the online platform. Recommendations are the Unique of decoration, sanitary, security, using the online platform for marketing. Create a good experience activity. Increase foreign language skills, use of technology, and good hosting. Provide laws and regulations relating to the short-term rentals for tourism, regulating the tax system in this business, security, and national stability.